Improving Student Achievement In Creative Integer Addition And Reduction Method Through Demonstrations With Equipment P Eraga Pinus Cards Fourth Grade Students Of Sdn 35 Parak Karakah East Padang District School Year 2015/2016 - Sirnayetti Sirnayetti (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Student difficulties experienced by students in the learning of mathematics, especially in the matter of addition and subtraction of integers, the cause is a fairly difficult subject matter. By using the method of demonstration using props pine students are expected to solve the problems associated with material addition and subtraction of integers . This research was conducted in the second semester of academic year 2015 / 2016. The time needed to study this class action is two months. This study uses classroom action research procedures planned two cycles, if not successful will resume the next cycle. The activities of each cycle consisting of: planning, action, observation, and reflection. The research subject of this class action is the fourth grade students of SD Negeri 35 Parak Karakah East Padang District Academic Year 2015/2016 , the fourth grade students of SD Negeri 35 Parak Karakah were 30 students comprising 13 girls and 17 boys. Observations carried out during the learning process by using observation sheet that was created earlier. Through Demonstration Method With Tool P eraga Pinus Cards Fourth Grade Students of SDN 35 Parak Karakah East Padang District Academic Year 2015/2016 is new learning for students of classes VI Elementary School 35 Parak Karakah East Padang District Academic Year 2015/2016, it can be a positive impact on the students themselves well in Improving student Achievement in summation Materials and Methods Through Integer Reduction Demonstration With Tool P eraga Pinus cards as well as increasing awareness among group members.